Sistem Penilaian Kinerja Dosen menggunakan Decision Maker Respondent Opinion Model - Ermatita Ermatita; Terttiaavini Terttiaavini (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
The subjectiveness of the performance assessment can not be avoided. The criteria determined for the performance assessment with human cognition is the subjectiveness phenomenon. This condition is being a challenge for the researcher to develop the performance assessment technique objectively. This method is a new approach to determine the performance assessment indicator with involving the employee to result in the realistic assessment. This model utilized the respondent opinion as a decision-maker to determine the relevance criteria and sub-criteria in the target achievement. The lecturer performance assessment is designed by utilizing the Decision-maker respondent opinion model (DMROM) algorithm. It is applicable to the criteria which contain the subjectiveness on the unlimited level. The data is arranged in the encoded item table to make it easy for the process of the calculation and sub-criteria which reach the support minimum limit. The algorithm is utilized the simple formula which could count the weight of each criterion and sub-criteria to the last level. The weight value on each sub-criteria will be accumulated as a sign of doing activities. The final result of this model is the list of the lecturer performance assessment who fulfilled the target or not as an input for the leader to take the decision.Keywords: Opini responden, Decision maker respondent opinion model, performance appraisal Subjektivitas pada penilaian kinerja tidak dapat dihindarkan. Penetapan kriteria untuk penilaian kinerja dengan kognisi manusia merupakan fenomena subjektif. Hal ini menjadi tantangan bagi peneliti untuk mengembangkan teknik penilaian kinerja secara objektif. Cara ini merupakan pendekatan baru untuk menentukan indikator penilaian kinerja dengan melilbatkan karyawan (responden) agar menghasilkan penilaian yang lebih realistis. Model ini menggunakan opini responden sebagai pengambil keputusan untuk menentukan kriteria dan subkriteria yang relevan dalam pencapaian target. Penilaian kinerja dosen dibangun dengan menggunakan algoritma Decision maker respondent opinion model (DMROM). Algoritma DMROM mampu diterapkan pada kriteria yang memiliki subkriteria pada level tak terbatas. Data disusun dalam Encoded item table untuk memudahkan proses perhitungan dan seleksi subkriteria yang mencapai batas minimum support. Algoritma ini juga menggunakan rumus sederhana yang dapat menghitung bobot pada masing-masing kriteria dan subkriteria di level ke-n. Nilai bobot pada masing-masing subkriteria akan diakumulasikan sebagai tanda melaksanakan kegiatan. Hasil akhir model ini adalah daftar penilaian kinerja dosen yang memenuhi target atau tidak sebagai masukan bagi pimpinan untuk mengambil keputusan. Kata Kunci : Opini responden, Decision maker respondent opinion model, Penilaian kinerja